Characterization of Class 1 Integrons from Pseudomonas aeruginosa That Contain the bla(VIM-2) Carbapenem-Hydrolyzing β-Lactamase Gene and of Two Novel Aminoglycoside Resistance Gene Cassettes - Poirel, Laurent (American Society for Microbiology, 2001)
Two clonally unrelated Pseudomonas aeruginosa clinical strains, RON-1 and RON-2, were isolated in 1997 and 1998 from patients hospitalized in a suburb of Paris, France. Both isolates expressed the class B carbapenem-hydrolyzing β-lactamase VIM-2 previously identified in Marseilles in the French Riviera. In both isolates, the bla(VIM-2) cassette was part of a class 1 integron that also encoded aminoglycoside-modifying enzymes. In one case, two novel aminoglycoside resistance gene cassettes, aacA29a and aacA29b, were located at the 5′ and 3′ end of the bla(VIM-2) gene cassette, respectively. The aacA29a and aacA29b gene cassettes were fused upstream with a 101-bp part of the 5′ end of the qacE cassette. The deduced amino acid sequence AAC(6′)-29a protein shared 96% identity with AAC(6′)-29b but only 34% identity with the aacA7-encoded AAC(6′)-I1, the closest relative of the AAC(6′)-I family enzymes. These aminoglycoside acetyltransferases had amino acid sequences much shorter (131 amino acids) than the other AAC(6′)-I enzymes (144 to 153 amino acids). They conferred resistance to amikacin, isepamicin, kanamycin, and tobramycin but not to gentamicin, netilmicin, and sisomicin.